Artistic manifestations as a mean of connection to the world outside the cloister: mural paintings in the Monastery of São Bento de Cástris - Conde, Antónia Fialho (2020)
S. Bento de Cástris Monastery was the first extramural monastic community in the town of Évora and the first Cistercian female community in southern Portugal. In the 16th century, as in other monasteries, its regular life underwent an intense reformation, because one of the main goals of the Ecumenical Council of Trent – held between 1545 and 1563 – was the regularization of monastic communities. Together with a spiritual renovation, influences of the Counter-reformation and of the Baroque culture were felt in the monastery artistic production (e.g. gilded woodwork, tiles, liturgical furniture, vestments, and frescoes). Mural paintings were particularly present in the cloistered spaces that were only accessible to the nuns (Refectory, High Choir, and Infirmary). Even today these spaces are not easely accessible for security reasons. The aim of this paper is to provide an insight view of the paintings and of the religious and cultural context on which they were produced